Building Information Modelling: Interoperability Issues - Kartikeayan, RS; Salmaliza, S; Mohd Rashid, Y (International Journal of Computer Sciences and Engineering, 2025)
There has been various interoperability issues among Building Information Modelling (BIM) and structural engineering design software programmes but there is still minimum researches to understand, test and evaluate the interoperability issues. This paper provides a better understanding of interoperability issues and its importance in providing more efficient interoperability among programmes for building information modelling to act as platform to exchange information among other disciplines. An attempt has been made by using Autodesk Revit as host of building information modelling whereas ESTEEM 9 and Orion 18 as structural engineering design software to identify interoperability issues arise due to information exchange. The interoperability issues were evaluated and causes of interoperability issues was identified. This research also offers an in-depth understanding of interoperability issues and importance of rectifying these interoperability issues in order for Architecture Engineering Construction (AEC) industry to adopt BIM completely for their projects. The ultimate outcome of this research offers the interoperability issues identified, the causes of interoperability issues and some suggestions to overcome these issues.